Green Supply Chain: Challenges and Practical Issues - Nadarajah, Gunalan SO; Sabri, Nur Aiedah Binti (International Journal of Supply Chain Management, 2016)
This conceptual paper aims to identify the challenges and practical issues in green supply chain management. Besides that, the established theory in adoption of green business practises are also pointed out to illustrate the complexities and practical issues arises in the process. The research emphases on the factors which hinder the success of green supply chain operations. The paper has revealed the challenges and issues arise due to conflicting objectives and limitations of measurement methods. The future research would be the opportunity to describe the market acceptance to the green businesses as well as practical measurement method to enable forecasting of the profits and strategic objective formulation. The findings will provide overviews on solving supply chain issues in implementing green supply chain practices. In the long run, the management practices will enhance the performance across the supply chain entities.   Keywords— Supply Chain, Green, Sustainability, Profitability, Government Role, Market